2006
DOI: 10.18848/1447-9532/cgp/v05i01/38849
|View full text |Cite
|
Sign up to set email alerts
|

Young Chinese Entrepreneurs in Australia: Migrant Networks in a New Land

Abstract: The study explores the phenomenon of young migrant Chinese entrepreneurs in Brisbane, Australia and the various ways in which they use networks to advance their business interests. While the concept of networking is an integral component of the Chinese way of doing business for Chinese entrepreneurs in Asian countries, the highly regulated business environment in Australia poses many challenges and restrictions to Chinese network reliance. The notions of 'entrepreneur', 'network' and 'entrepreneurial networks'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…While the culturalist explanations provide succinct conceptualizations they are flawed by their failure to account for the much broader context in which immigrant entrepreneurs are embedded (Gao, ; Jones & Ram, ). This flaw is also reflected in the failure to explicitly distinguish immigrant entrepreneurs from other segments of ethnic entrepreneurs who are embedded in dissimilar and changing contexts (e.g., Batonda & Perry, ; Kariv et al, ; Lund et al, ).…”
Section: Research On Immigrant Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…While the culturalist explanations provide succinct conceptualizations they are flawed by their failure to account for the much broader context in which immigrant entrepreneurs are embedded (Gao, ; Jones & Ram, ). This flaw is also reflected in the failure to explicitly distinguish immigrant entrepreneurs from other segments of ethnic entrepreneurs who are embedded in dissimilar and changing contexts (e.g., Batonda & Perry, ; Kariv et al, ; Lund et al, ).…”
Section: Research On Immigrant Entrepreneurshipmentioning
confidence: 99%
“…In this study, these Chinese immigrant entrepreneurs, who are first‐generation immigrants emigrating from mainland China since 1980s, are referred to as new Chinese immigrant entrepreneurs (NCIEs) to distinguish them from other segments of ethnic Chinese entrepreneurs. This approach follows the tradition of mainstream research on Chinese immigrants (Chan & Koh, ; Gao, ; Ren & Liu, ; Zhou & Liu, ), although not all studies make this distinction (e.g., Batonda & Perry, ; Lund, Woods, Hibbins, & Barker, ).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed previously, several studies have shown that immigrant entrepreneurs lack language competency (e.g., Collins & Low, 2010;Lund et al, 2006;Mora & Dávila, 2005). This may be why a lack of language competency creates a barrier to communicating with others, which is part of psychic distance (Johanson & Wiedersheim-Paul, 1975).…”
Section: Immigrant Entrepreneurs' Cross-cultural Capabilities Of Socimentioning
confidence: 95%
“…Family and community networks are important to these individuals, as this is a mechanism for building trust and reliability (Collins, 2002;Lund, Woods, Hibbins, & Barker, 2006). With respect to networks, researchers discovered that Chinese immigrant entrepreneurs in Australia can make their own businesses successful by leveraging their networks, which contributes to economic outcomes (Dai et al, 2011).…”
Section: Recently With a Growing Chinese Immigrant Population And Thmentioning
confidence: 99%